Analysis of Leadership Style at Bank Sumedang - Helles Amanda (CV. Ulil Albab Corp, 2024)
This study aims to determine the implementation of Leadership Style at Bank Sumedang Cimalaka Branch. The benefit of this research is to provide positive and constructive thinking references for practical solutions related to the research title.The research method used in this research is descriptive using a qualitative analysis study approach. The data collection techniques used are library research, field studies (observations, interviews, and documentation). While the data processing procedure used the data analysis model of Miles and Huberman. Informants in this study were determined using a purposive sampling method, namely as many as 10 people.In the decision-making process, subordinates are always involved in decision-making which is carried out through a process of deliberation, the leader who is responsible for providing good decision results for Bank Sumedang. The final results of this study conclude that the Leadership Style at Bank Sumedang, Sumedang Branch refers to democratic leadership, but in practice there are still obstacles so that leadership at Bank Sumedang, Cimalaka Branch, is considered not optimal.Based on the results of the study, the researcher recommends several suggestions as an effort to improve leadership quality, namely leaders to improve communication with subordinates so that differences in views between subordinates and superiors can be avoided. Bank Sumedang namely honesty, responsibility, discipline, prudent, cooperation, passion, caring.